2022
DOI: 10.3390/jrfm15050200
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Business Valuation: Methodical Implementation in the Valuation Practice

Abstract: The simulation-based company valuation values a company on the basis of the risks actually present in the company without having to derive them from the capital market data. The simulation-based company valuation takes into account the market imperfections, such as the probability of insolvency or the lack of diversification, and fulfils the legal requirements and auditing standards for a company valuation. The simulation-based company valuation is an alternative to the CAPM-based company valuation, which, und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The general approach in risk mitigation has also been found in another research findings such as Sivitska and Makhmudov (2020) where the study identified that factors such business risk, operational risk, market risk, economic risk, industry risk, revenue growth, competition, diversification, employee relation are the main factors in determining risk in business valuation. Other studies include those by Ernst (2022), Scheurwater (2020), andGleißner (2019).…”
Section: Discussionmentioning
confidence: 99%
“…The general approach in risk mitigation has also been found in another research findings such as Sivitska and Makhmudov (2020) where the study identified that factors such business risk, operational risk, market risk, economic risk, industry risk, revenue growth, competition, diversification, employee relation are the main factors in determining risk in business valuation. Other studies include those by Ernst (2022), Scheurwater (2020), andGleißner (2019).…”
Section: Discussionmentioning
confidence: 99%
“…The approach suggested has the same basis in seminal earnings valuation theory (Ohlson 2005) as traditional valuation using the Capital Assets Pricing Model to estimate the cost of equity capital and variants thereof, such as the Fama and French (2015) five-factor model. Ernst (2022) acknowledges this situation throughout his paper. Hence, Ernst (2022) illustrates that in addressing the challenge of valuing non-listed entities, researchers have a responsibility to anchor their work in seminal theory.…”
Section: Implications Arising From the Paper About Simulation-based V...mentioning
confidence: 98%
“…Hence, Ernst (2022) illustrates that in addressing the challenge of valuing non-listed entities, researchers have a responsibility to anchor their work in seminal theory. Ernst (2022) contributes to the empirical finance literature via its sound motivation. Unlisted entities have always been important.…”
Section: Implications Arising From the Paper About Simulation-based V...mentioning
confidence: 99%
See 1 more Smart Citation
“…Gleißner, 2022; Dorfleitner and Gleißner, 2018; Dorfleitner, 2022). This method specifically allows the derivation of risk-adequate discount rates from a stochastic planning model and is thus based on a risk analysis, which describes uncertain planning premises through probability distributions (“simulation-based valuation”, see Ernst, 2022). Based on Dorfleitner and Gleißner (2018), we assume that two cash flows (trueCF1,trueCF2) to the valuation object (investment O ) (at the same point in time t ) have the same value ( V ) if they match the expected value E (CFt) and in the chosen risk measure R (CFt), e.g.…”
Section: A New Approach To Player Valuationmentioning
confidence: 99%